Acute Coronary Syndromes: A Role of Immune System - Lorenzova, Alena; Penicka, Martin (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2008)
Immune mechanisms play a role in destabilization of atherosclerotic plaque. Vulnerability of the plaque depends on the features of lipid core, stability of the fibrous cap, macrophage and neutrophil infiltration. Also products of leukocytes like metalloproteinases and myeloperoxidase may destabilize the plaque. Destabilized plaque easily ruptures event after minor impact. After plaque rupture, when myocardial infarction happens, immune mechanisms play a role not only in healing, but also may destructively influence left ventricle remodeling. Tumor necrosis factor-α, transforming growth factor-β, toll like receptors and cyclooxygenase are among the most investigated molecules that are thought to influence left ventricular remodeling nowadays. Also autoimmunity (antibodies against contractile proteins) adversely contributes to myocardial remodeling.
Keywords: autoimmunity